Japanese Compounds with the Lexeme “Mouth”: Word Formation and Meanings - Sudipa, Made Henra Dwikarmawan; Meilantari, Ni Luh Gede; Widiastika, I Wayan Wahyu Cipta (Bina Nusantara University, 2024)
In Japanese, the lexeme ‘mouth’ can be written using kanji 口 read as ‘kuchi’. It is a commonly used character that includes idiomatic expressions and compound words. Although ‘kuchi’ means ‘mouth’ and functions as a noun, it can change into different forms and meanings. Therefore, this research analyzed the forms and meanings of Japanese compound words formed by the lexeme ‘mouth’. The data was collected from Japanese newspaper articles from Asahi Shinbun in sentences using various compounds with the lexeme ‘mouth’ through observation and note-taking techniques. Then, the data was analyzed using the distribution method with the expansion technique. The morphology theory by Kageyama (2016) and Katamba (2018) is used to analyze Japanese compounds' construction and meaning. The results show that 120 Japanese compound words are formed by the lexeme ‘mouth’. There are three forms of compounds based on various word classes including compound nouns (consisting of noun + noun, adjective + noun, and verb + noun), compound adjectives (noun + adjective), and compound verbs (noun + verb). Based on its meaning, it can be classified into two categories, endocentric and exocentric meaning. By offering a thorough analysis of Japanese compound words containing the lexeme kuchi ‘mouth’, this research provides insights into Japanese morphosemantics by highlighting a single lexeme adopted within the compound, especially regarding forms and meanings of compound words. This research contributes to morphological theory application within Japanese studies and can be used for similar research in the future.